IMPLEMENTASI SUPERVISI AKADEMIK OLEH KEPALA SEKOLAH UNTUK MENINGKATKAN KINERJA GURU SMPN 1 SELUAS - Ngutini, Ngutini; Sukmawati, Sukmawati; Syukri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the implementation of academic supervision by the principal to improve teacher performance at SMP Negeri 1 Seluas. This form of research uses qualitative methods. The research subjects were 3 people, namely the Principal, Deputy Principal for Curriculum and Teachers. Methods of collecting data with interviews, documentation, and observation. Data analysis uses data reduction, data display and verifications. The technique of checking the validity of the data is by testing credibility, transferability, dependability and confirmability. The results of the study can be concluded: 1) planning can be done through: (1) formulating a vision and mission, and compiling supervision guidelines, 2) implementation is carried out through: determining supervisors, distributing supervision schedules, and involvement of all parties, 3) follow-up is carried out through: evaluation and reflection, and involve all parties, 4) obstacles to academic supervision, among others: academic supervision cannot be carried out according to schedule, teachers are not ready to be supervised, and limited facilities and infrastructure, and 5) efforts to overcome obstacles include: rescheduling academic supervision, teachers using media and teaching aids, prioritizing teachers supervised in using school facilities and infrastructure.